The impact of risk management in credit rating agencies - A. Seetharaman; Vikas Kumar Sahu; A. S. Saravanan; John Rudolph Raj; Indu Niranjan (Risks, 2017)
An empirical study was conducted to determine the impact of different types of risk on the performance management of credit rating agencies (CRAs). The different types of risks were classified as operational, market, business, financial, and credit. All these five variables were analysed to ascertain their impact on the performance of CRAs. In addition, apart from identifying the significant variables, the study focused on setting out a structured framework for future research. The five independent variables were tested statistically using structural equation modelling (SEM). The results indicated that market risk, financial risk, and credit risk have a significant impact on the performance of CRAs, whereas operational risk and business risk, though important, do not have a significant influence. This finding has a significant implication for the examination and inter-firm evaluation of CRAs.
Keywords: 330; credit rating financial risk; credit risk; business risk; operational risk; market risk